Pengaruh Manajemen Pendidikan Inklusif terhadap Layanan Anak Berkebutuhan Khusus di SD Zion Palu: The Influence of Inclusive Education Management on Services for Children with Special Needs at Zion Elementary School, Palu - Censia Madelin Krisanti Muharam; Yusdin Bin. M. Gagaramusu; Dyah Rahmawati; Rizal Rizal; Nurlinda Nurlinda (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
This study aims to determine the effect of inclusive education management on services for children with special needs (ABK) at Zion Elementary School, Palu. The study used a quantitative, comparative, causal (ex post facto) design, which focuses on cause-and-effect relationships based on conditions that have occurred without experimental treatment. The study population was the principal and all 17 class teachers at Zion Elementary School, Palu, who were also sampled through a saturated sampling technique. Data collection techniques included a questionnaire as the main instrument, along with observation, interviews, and documentation to strengthen the research results. Data analysis was carried out using descriptive analysis to describe the conditions of the research variables and inferential analysis using simple linear regression in SPSS to test the hypothesis. The results showed that the significance value was 0.021 < 0.05, indicating that H1 was accepted and H0 was rejected. This means that inclusive education management significantly influences services for children with special needs at Zion Elementary School in Palu. This finding indicates that the quality of ABK services is greatly influenced by the effectiveness of inclusive education management, especially in planning, implementation, and evaluation of learning. Thus, the better the implementation of inclusive education management, the more effective the services provided to children with special needs, both academically and socially. The results of this study are expected to serve as a basis for improving the quality of inclusive education services in elementary schools.